Fibromyalgia syndrome – current concepts - H.P. Meyer (South African Family Practice)
Fibromyalgia (FM) is a recognised chronic pain syndrome that is diagnosed without any special investigations. This syndrome constitutes widespread pain in a specific distribution, for a specific period of time, as well as tenderness over at least 11 out of 18 clearly defined tender points. This syndrome is a common cause of other conditions commonly encountered in general practice and this article provides a practical and clinical approach to diagnosis and treatment.